2018
DOI: 10.5539/gjhs.v10n3p42
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Determine the Occupational Stress Level and Professional Burnout in Special School Teachers Working in Private and Government Schools

Abstract: Background and Objective: Healthy work environment is required to provide high quality teaching. Few studies regarding occupational stress and burnout in Indian schools have been conducted. The study aims to determine and compare the occupational stress level and professional burnout in teachers working in private and government schools. 120 private school teachers and 120 government school teachers recruited for this study. Methods:Chi square test, Student independent t test and ANOVA used for data analysis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Job-related stress is widespread across employees ( Asamoah-Appiah and Aggrey-Fynn, 2017 ; Ojwang, n.d. ; Ogba et al, 2019 ), affecting about 70–89% of educators worldwide ( Reddy and Anuradha, 2013 ; Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ). Stress occurs when there is an activation in the body due to mismatch between the environmental demands and the ability to cope with such demands ( Reddy and Anuradha, 2013 ), causing significant, cognitive, physical and/or emotional impacts on health and well-being ( Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ; AbuMadini and Sakthivel, 2018 ). Job-stress is a negative subjective feeling experienced in occupational situation ( Ogba et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job-related stress is widespread across employees ( Asamoah-Appiah and Aggrey-Fynn, 2017 ; Ojwang, n.d. ; Ogba et al, 2019 ), affecting about 70–89% of educators worldwide ( Reddy and Anuradha, 2013 ; Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ). Stress occurs when there is an activation in the body due to mismatch between the environmental demands and the ability to cope with such demands ( Reddy and Anuradha, 2013 ), causing significant, cognitive, physical and/or emotional impacts on health and well-being ( Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ; AbuMadini and Sakthivel, 2018 ). Job-stress is a negative subjective feeling experienced in occupational situation ( Ogba et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Reddy and Anuradha, 2013 ; Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ; AbuMadini and Sakthivel, 2018 ; Ogba et al, 2020 ; Chadha et al, 2012 ; Peltzer et al, 2009 ; Sumathy and Sudha, 2013 ) It manifests in teachers as distasteful emotions such as worry, irritation, anger, frustration and depression resulting from work experiences. ( Reddy and Anuradha, 2013 ; Sukumar and Kanagarathinam, 2016 ; Okwaraji and Aguwa, 2015 ; Manabete et al, 2016 ; AbuMadini and Sakthivel, 2018 ; Ogba et al, 2020 ; Chadha et al, 2012 ; Peltzer et al, 2009 ; Sumathy and Sudha, 2013 ; Pereira-Morales et al, 2017 ) Teachers' stress is also results in emotional consequences as depression, anxiety, burnout and decreased job satisfaction; ( Ogba et al, 2019 ; Manabete et al, 2016 ; AbuMadini and Sakthivel, 2018 ; Ogba et al, 2020 ; Chadha et al, 2012 ; Peltzer et al, 2009 ; Sumathy and Sudha, 2013 ; Pereira-Morales et al, 2017 ; Yang et al, 2015a ; Major, 2012 ; Cappe et al, 2017 ) professional consequences including absenteeism, inefficiency, attrition, and suicidal and attempt ( Reddy and Anuradha, 2013 ; Zarafshan et al, 2013 ; Kebbi, 2018 ; Atiyat, 2017 ; Gersten et al, 2001 ; Kuvaeva, 2018 ; Bush, 2010 ; Davis, n.d. ; Arun et al, 2017 ; Hamlett, 2016 ). It also results in physiological symptoms such as headache, impaired immune function, musculoskeletal pains, and cardiovascular diseases ( Ogba et al, 2019 ; Yang et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that the teaching profession have many job demands and therefore musculoskeletal disorder develops over time and is caused by either the work demands or by the working environment. [15] This might explain the high prevalence observed in the present study. However, lower rates have been reported in similar studies carried out in India where the point and overall prevalence of LBP were 28% and 23%, respectively, [9] Japan where the total prevalence of LBP was 20.4% in male and 23.2% in female teachers, [16] Turkey, where 60.3% of teachers had work-related pain; low back pain was the commonest (74.9%).…”
Section: Prevalence Of Lbpmentioning
confidence: 46%
“…However, the explanation of their feeling of anxiety was high. Hence, we need further investigation required to recognize factors that lead to pressure and burnout in legislative and non-public schools (Doss et al, 2018) Our investigation indicated that around 27% of undergrads in India appeared in danger IA, while few had IA; furthermore, the outcomes demonstrated that in danger IA was emphatically connected with the two ages more than 20 and gaming on the internet. This examination explained the pervasiveness of IA and in danger IA and the hazard factors among understudies in India.…”
Section: Discussionmentioning
confidence: 84%